Effects of nitrogen rates and boron-containing biostimulant application on sunflower (Helianthus annuus L.) yield and physiological responses under drought conditions - Virág, István Csaba; Csajbók, József; Lelesz, Judit Éva; Rátonyi, Tamás; Varga, Melinda (Acta Agraria Debreceniensis, 2026)
The objective of the study was to evaluate the effects of nitrogen fertilization and the foliar-applied biostimulant Activstart Szántóföldi B (hereinafter BS) on sunflower (Helianthus annuus L.) production under drought conditions. The experiment was established in 2025 in the Újfehértó region, on acidic, low-humus, gleyic brown forest soil. Nitrogen supply was examined at rates of 0, 30, 60, and 90 kg ha-1, with biostimulant-treated (applied twice) and untreated control plots. Crop status was monitored during the growing season using SPAD and NDVI measurements, while treatment effects were evaluated based on yield results. Based on yield data, nitrogen fertilization resulted in an almost linear yield increase; however, the rate of increase declined at higher doses. BS application alone produced a significant yield increase of approximately 16%, and in combination with nitrogen resulted in higher yields at all nutrient levels. The most balanced performance was achieved with the combined application of 60 kg ha-1 nitrogen and BS. SPAD measurements showed no clear relationship between chlorophyll content and nitrogen rates, while biostimulant treatments resulted in more stable values, particularly at lower N levels. NDVI values were only moderately affected by treatments.